XYLAZINE-KETAMINE ANAESTHESIA; COMPARATIVE STUDIES IN MALE AND FEMALE CANE RATS (THRYONOMYS SWINDERIANUS) - A, Olatunji-akioye; N, Ojiaka H; S, Samuel E. (International Journal of Pharmacy and Pharmaceutical Sciences, 2017)
Objective: Domestication of the Cane rats is on-going globally and might replace the conventional rodents used in biomedical research in future. However, the paucity of information on adequate anaesthesia vis-a-vis xylazine-ketamine drug combination in the male and female Cane rats warranted this study. Methods: Six adult Cane rats {1.8Â±0.7 kg body weights (bwt.)} assigned into group A (Female) and group B (Male) of three rats each was used for the study. Each animal was premedicated with atropine sulphate (0.05 mg/kg bwt), and later administered xylazine (10 mg/kg bwt) and ketamine (100 mg/kg bwt) intramuscularly. Meanwhile, anaesthetic characteristics and physiologic indices of anaesthesia were monitored. Results: Results obtained showed that the physiologic indices; open eyelids, smooth induction and recovery, skeletal muscle relaxation and somatic analgesia were observed in all the animals, however, the anaesthetic indices; time to induction, time to standing, duration of analgesia and duration of recumbency showed marked sex variations. The mean values for the duration of analgesia and recumbency were significantly elevated (P<0.05) in group B as compared with group A. Similar trend was seen for time to standing, but, it was non-significant (P>005). However, time to induction mean value for group A was non-significantly increased (P>005) when compared with group B. The heart rate, respiratory rate and rectal temperature mean values decreased in both groups non-significantly (P>0.05). Conclusion: Conclusively, the xylazine-ketamine combination produced anaesthesia in Cane rat and the combination is more tolerated in the male Cane rats than the female Cane rats.